Pengaruh Senam Otak terhadap Fungsi Kognitif pada Lansia di Panti Sosial Tresna Werdha Budi Luhur Provinsi Jambi - Aprilia, Sherli; Mekeama, Luri; Nasution, Riska Amalya (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of the research was to determine the effect of brain exercises on cognitive function in the elderly at the Tresna Werdha Budi Luhur Social Home, Jambi Province. This type of research is quantitative with a quasi-experimental design approach, pretest-posttest control group design. This research was conducted at the Tresna Werdha Budi Luhur Social Home, Jambi Province.The sampling method was purposive sampling of 22 people. 11 respondents in the control group and 11 respondents in the intervention group. Data measurement uses MMSE. Bivariate analysis used the Wilcoxon Rank Test and the Man Whitney test. The research results showed that the age frequency distribution of respondents was mostly elderly, female, and had elementary school education. The cognitive function of the pretest intervention group was mostly mild and severe cognitive function. The pretest and posttest results showed a significant increase, so that there was an influence of brain exercise on cognitive function in the elderly, with a p value = 0.002 (< 0.05). There was a significant effect of increasing cognitive function before and after being given brain exercises at PSTW. It is hoped that PSTW can develop brain exercises to improve the cognitive function of the elderly.